ROLE OF BIOMARKERS AS PREDICTORS OF INFECTION AND DEATH IN NEUTROPENIC FEBRILE PATIENTS AFTER HEMATOPOIETIC STEM CELL TRANSPLANTATION. - Karim Massaro; Silvia F Costa (Mediterranean Journal of Hematology and Infectious Diseases)
An ideal marker in the neutropenic population after HSCT is the one which indicates the onset of fever, or at most up to 24 hours after its onset, the patients under potential risk for infection due to bacterial and fungi and mortality. Several biomarkers have been used in HSCT patients in the last decade. However, it seems that C-RP and Il-6 are the most useful markers to early detected infection and risk for death.